2020
DOI: 10.3390/ani10030438
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immune Responses of Skin Mucosa in Common Carp (Cyprinus Carpio) Fed a Diet Supplemented with Galactooligosaccharides

Abstract: Galactooligosaccharides (GOS) are well-known immunomodulatory prebiotics. We hypothesize that GOS supplemented in feed modulates innate immune responses in the skin-associated lymphoid tissue (SALT) of common carp. The aim of this study was to determine the impact of GOS on mRNA expression of the immune-related genes in skin mucosa. During the feeding trial, the juvenile fish (bodyweight 180 ± 5 g) were fed two types of diet for 50 days: control and supplemented with 2% GOS. At the end of the trial, a subset o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 80 publications
0
17
0
Order By: Relevance
“…Interestingly, the skin also showed notable expression levels for some isoforms, particularly crp3–5 . A few studies previously reported the expression of crp s in skin from zebrafish [ 25 ], Cyprinus carpio [ 35 , 41 ], Oplegnathus fasciatus [ 36 ], and Sebastes schlegelii [ 38 ] and its presence in skin mucus from Gadus morhua [ 42 ], Raja kenojei [ 43 ], Cyclopterus lumpus [ 44 ], and Tilapia mossambica [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the skin also showed notable expression levels for some isoforms, particularly crp3–5 . A few studies previously reported the expression of crp s in skin from zebrafish [ 25 ], Cyprinus carpio [ 35 , 41 ], Oplegnathus fasciatus [ 36 ], and Sebastes schlegelii [ 38 ] and its presence in skin mucus from Gadus morhua [ 42 ], Raja kenojei [ 43 ], Cyclopterus lumpus [ 44 ], and Tilapia mossambica [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…The fish skin is covered with a mucosal surface, as the outer layer, that is always in contact with the surrounding environment. It serves as a major immunological barrier and is considered the first line of defense against pathogens and other imminent stressors [ 49 , 50 , 51 ]. In addition, mucus, the glycopolymers secretion covering the mucosa, harbors a variety of antibacterial components, including proteins and enzymes, such as lysozyme and proteolytic enzymes, immunoglobulins, complement proteins, lectins, and C-reactive proteins [ 52 , 53 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Such an effect was also observed in a study performed in crayfish: crayfish susceptibility to the viral White-spot disease was reduced while the expression of hemocyte-associated crayfish CTL (X2C306-1) was simultaneously upregulated following the probiotic gavage of Bacillus amyloliquefaciens [ 138 ]. Further positive effects of carbohydrate supplements were demonstrated in lentinan-rich shiitake mushrooms gavage in a rat model of human dyslipidemia [ 139 ], probiotic glucan gavage in carp [ 140 ], and mannoprotein supplementation in adult and aging dogs [ 141 ].…”
Section: Discussionmentioning
confidence: 99%